A posteriori initial imperfection identification in shell buckling problems - Stull, Christopher J.; Earls, Christopher J.; Aquino, Wilkins (Computer methods in applied mechanics and engineering, 2008)
The current research seeks to demonstrate that an inverse solution approach, leveraging nonlinear finite element analysis with a divide and conquer type stochastic search algorithm, can identify the presence of localized denting imperfections in cylindrical shell structures. This imperfection field identification is achieved using rather sparse displacement measurements taken at safe, service loading conditions. Both the existence and nature of the imperfection field present in a given shell structure instance are determined. These inferred imperfections are subsequently used to make reasonably accurate predictions regarding the actual shell structure strength at ultimate loading.